Microbial responses to herbivory-induced vegetation changes in a high-Arctic peatland - Bender, Kathrin M.; Svenning, Mette M.; Hu, Yuntao; Richter, Andreas; Schuckel, Julia; Jorgensen, Bodil; Liebner, Susanne (Jun.-Prof. Dr.); Tveit, Alexander T. (Polar Biology, 2021)
Herbivory by barnacle geese (Branta leucopsis) alters the vegetation cover and reduces ecosystem productivity in high-Arctic peatlands, limiting the carbon sink strength of these ecosystems. Here we investigate how herbivory-induced vegetation changes affect the activities of peat soil microbiota using metagenomics, metatranscriptomics and targeted metabolomics in a comparison of fenced exclosures and nearby grazed sites. Our results show that a different vegetation with a high proportion of vascular plants developed due to reduced herbivory, resulting in a larger and more diverse input of polysaccharides to the soil at exclosed study sites. This coincided with higher sugar and amino acid concentrations in the soil at this site as well as the establishment of a more abundant and active microbiota, including saprotrophic fungi with broad substrate ranges, like Helotiales (Ascomycota) and Agaricales (Basidiomycota). A detailed description of fungal transcriptional profiles revealed higher gene expression for cellulose, hemicellulose, pectin, lignin and chitin degradation at herbivory-exclosed sites. Furthermore, we observed an increase in the number of genes and transcripts for predatory eukaryotes such as Entomobryomorpha (Arthropoda). We conclude that in the absence of herbivory, the development of a vascular vegetation alters the soil polysaccharide composition and supports larger and more active populations of fungi and predatory eukaryotes.